(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, the cause and the improvement measure of malfunction in the automatic residential kitchen fire extinguishing system were sought by associating with the theory of market failure. First, in the perspective of monopoly, installing the kitchen fire extinguisher by the constructor during the apartment construction, the monopoly is made. Therefore, as improvement measure, it is necessary to allow free competition among the businesses by guaranteeing the consumer’s choice. Second, in the perspective of externality, there is a problem of making profit of the business by inducing the consumer to receive the charged repair of the defective product by the problem occurred by ageing. Therefore, it is necessary to grant the authority to collect and inspect the fire-fighting supplies under distribution. Finally, in the perspective of information asymmetry, the business has not informed the information of defective products to the consumers. Therefore, the information asymmetry occurred between the enterprise and the consumer should be reduced by disclosing the type approval and the acceptance criteria of product inspection. For the follow-up research, the research that is seeking out the improvement measure in order to guarantee the safe life is required by examining if other firefighting supplies are the reliable product or not.